Relationship between the state of tongue hygiene and the number of residual teeth in convalescent-ward inpatients, cross- sectional study - Kanako Hayashi; Maya Izumi; Ayaka Isobe; Yuhei Mastuda; Sumio Akifusa (BMC, 2019)
Abstract Background The changed disease landscape in Japan because of an increasing aging population has contributed to an increase in convalescent inpatients, warranting important considerations of their oral care needs. However, information on the oral state of these inpatients is scarce. We evaluated the correlation between the number of residual teeth and tongue hygiene state in these inpatients. Methods This cross-sectional study included convalescent-ward inpatients, aged 34-100 years. The study was conducted between April 2017 and March 2018 in Kitakyushu, Japan. Data regarding age, sex, number of residual teeth, odontotherapy requirement, medications with oral side effects, and the reason for hospitalization, were collected. Oral hygiene level was assessed using the Oral Health Assessment Tool (OHAT). The correlation between each element of OHAT and the number of residual teeth was analyzed using Pearson's correlation analysis. The risk of a remarkable tongue state was analyzed using binominal logistic regression analysis. Results Correlations were observed between the number of residual teeth and OHAT subscales, including tongue, saliva, and dentures. A significantly higher percentage of inpatients with ≤19 teeth had a tongue state score of 1 or higher, compared with those with ≥20 teeth. (78.6% vs 57.7%, p = 0.047). In inpatients with ≥20 teeth, the remarkable saliva state significantly increased the risk of the remarkable tongue state by 10.49-fold (95% confidence interval = 2.86-38.51), after adjusting for potential confounders. Conclusion Poor tongue hygiene is associated with the number of teeth and salivary state in convalescent-ward inpatients. Inpatients with ≤19 teeth had a higher risk of poor tongue hygiene, regardless of the salivary condition, as assessed using OHAT.